HOSPEDEIRAS ALTERNATIVAS DAS TRÊS PRINCIPAIS ESPÉCIES DE PERCEVEJOS SUGADORES (HEMIPTERA) ASSOCIADOS À SOJA, GLYCINE MAX (L.) MERRIL (FABACEAE), EM UM CULTIVO ORGÂNICO NO NOROESTE DO RIO GRANDE DO SUL - Medeiros, Lenice; Woitechumas, Letícia; Megier, Gabriela (Salão do Conhecimento, 2013)
Resumo